Comparison of Urine and Blood Zinc Levels of Futsal Players Before and After The Match - KAYA, METIN (Asian Journal of Chemistry, 2010)
This study is concerned the determination of the changes in urine and blood zinc levels of the players before and after a futsal match. The mean pre and post match concentrations were found as 1.4370 ± 0.3808 and 3.1230 ± 2.1627 μg/dl which marked a statistically significant increase. The results were in good accordance with literature.